The Status of Children Born Out of Wedlock in Relation to Guardianship and Inheritance Post-Constitutional Court Decision - Desi Amalia; Sumarni Sumarni; Iqbal Tanjung; Tajul Muttaqin (Jurnal Hukum Replik, 2026)
Constitutional Court Decision Number 46/PUU-VIII/2010 has brought significant changes to the legal status of children born out of wedlock, particularly concerning guardianship and inheritance rights. This study aims to analyze the juridical implications of the decision on the civil rights of children born out of wedlock, especially in terms of guardianship and inheritance. The research employs a normative juridical method with a legislative and judicial decision approach, complemented by analysis of legal doctrines and relevant case studies. The findings indicate that following the Constitutional Court ruling, children born out of wedlock who can demonstrate biological ties to their fathers through scientific and technological evidence and/or other legally recognized proofs, are entitled to recognized civil rights, including guardianship and inheritance rights. Nevertheless, practical implementation continues to face challenges, primarily regarding the proof of biological relationships and social acceptance. Therefore, there is a need for regulatory harmonization and a more progressive understanding by law enforcement officers in upholding the rights of children born out of wedlock post-Constitutional Court ruling.Keywords: Children born out of wedlock, guardianship, inheritance, Constitutional Court decision, civil rights.